Takeover Threats and Managerial Myopia - Stein, Jeremy C. (Journal of Political Economy, 1988)
This paper examines the familiar argument that takeover pressure can be damaging because i t leads managers to sacrifice long-term interests in order to boost c urrent profits. If stockholders are imperfectly informed, temporarily low earnings may cause the stock to become undervalued, increasing t he likelihood of a takeover at an unfavorable price; hence the manage rial concern with current bottom line. The magnitude of the problem d epends on a variety of factors, including the attitudes and beliefs o f shareholders, the extent to which corporate raiders have inside inf ormation, and the degree to which managers are concerned with retaini ng control of their firms. Copyright 1988 by University of Chicago Press.